2019
DOI: 10.1155/2019/3276156
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenicity and Transcriptome Analysis of Methicillin-Resistant Staphylococcus aureus in Response to Water Extract of Galla chinensis

Abstract: Aim. Antibiotic abuse contributes to the emergence of methicillin-resistant Staphylococcus aureus (MRSA). It is increasingly important to screen new antimicrobial agents for the management of MRSA infections. G. chinensis, a nontoxic Chinese herbal medicine, is considered a potential antibacterial agent. The aim of this study was to investigate the bactericidal effects of the aqueous extracts of G. chinensis on MRSA. The potential mechanisms of G. chinensis aqueous extract inhibition of the pathogenicity of MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Global transcript analyses of in vitro and infection-derived S. aureus biofilms, e.g., using RNA sequencing approaches, should offer a more complete picture in the future. At present the effects of antimicrobial interventions ( Singh et al, 2019 ; Wu et al, 2019 ), responses to sublethal disinfectant challenges ( Slany et al, 2017 ), the importance of iron homeostasis in MRSA viability ( Abouelhassan et al, 2018 ) and the differential response to immune cells ( Scherr et al, 2013 ) have been reported for S. aureus following transcript analysis of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Global transcript analyses of in vitro and infection-derived S. aureus biofilms, e.g., using RNA sequencing approaches, should offer a more complete picture in the future. At present the effects of antimicrobial interventions ( Singh et al, 2019 ; Wu et al, 2019 ), responses to sublethal disinfectant challenges ( Slany et al, 2017 ), the importance of iron homeostasis in MRSA viability ( Abouelhassan et al, 2018 ) and the differential response to immune cells ( Scherr et al, 2013 ) have been reported for S. aureus following transcript analysis of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…ATCC29213, ASyycF ATCC29213, MRSA, and ASyycF MRSA strains were cultured in TSB at 37 • C as previously described [28]. Growth curves were measured at OD 600 every hour.…”
Section: Detection Of Bacterial Growth and Biofilm Assessmentmentioning
confidence: 99%
“…After rinsed twice with PBS, the bacterial cells in the biofilm were labelled with SYTO9 (Invitrogen, Carlsbad, CA) for 15 min. CLSM, TSP SP2; Leica, Solms, Germany) was then performed to tested EPS in each group (Wu et al 2019d). After that, lasers of 480-500 nm for SYTO 9 stain (green fluorescence) and 605-635 nm lasers for propidium iodide (red fluorescence) were applied to differentiate live and dead cells for live/dead ratio.…”
Section: Primersmentioning
confidence: 99%